Evaluation of loading parameters for murine axial tibial loading: Stimulating cortical bone formation while reducing loading duration. Issue 2 (9th October 2017) - Sun, David; Brodt, Michael D.; Zannit, Heather M.; Holguin, Nilsson; Silva, Matthew J.
ABSTRACT: Classic studies in bone mechanobiology have established the importance of loading parameters on the anabolic response. Most of these early studies were done using loading methods not currently in favor, and using non‐murine species. Our objective was to re‐examine the effects of several loading parameters on the response of cortical bone using the contemporary murine axial tibial compression model. We subjected tibias of 5‐month old, female C57Bl/6 mice to cyclic (4 Hz) mechanical loading and examined bone formation responses using dynamic and static histomorphometry. First, using a reference protocol of 1, 200 cycles/day, 5 days/week for 2 weeks, we confirmed the significant influence of peak strain magnitude on periosteal mineralizing surface (Ps.MS/BS) and bone formation rate (Ps.BFR/BS) ( p  < 0.05, ANOVA). There was a significant induction of periosteal lamellar bone at a lower threshold of approx. −1, 000 μϵ and a transition from lamellar‐woven bone near −2, 000 μϵ. In contrast, on the endocortical surface, bone formation indices did not exhibit a load magnitude‐dependent response and no incidence of woven bone. Next, we found that reducing daily cycle number from 1, 200 to 300 to 60 did not diminish the bone formation response ( p  > 0.05). On the other hand, reducing the daily frequency of loading from 5 consecutive days/week to 3 alternate days/week significantly diminished the periosteal response, from a loading‐induced increase in Ps.MS/BS of 38% (loaded vs. control) for 5 days/week to only 15% for 3 days/week ( p  < 0.05). Finally, we determined that reducing the study duration from 2 to 1 weeks of loading did not affect bone formation outcomes. In conclusion, cyclic loading to −1, 800 μϵ peak strain, at 4 Hz and 60 cycles/day for 5 consecutive days (1 week) induces an increase in periosteal lamellar bone formation with minimal incidence of woven bone in 5‐month‐old C57Bl/6 female mice. Our results provide a basis for reduction of loading duration (daily cycles and study length) without loss of anabolic effect as measured by dynamic histomorphometry. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:682–691, 2018.